Chicken manure-based organomineral fertilization improves nutrient use efficiency and reduces greenhouse gases (GHGs) emissions in maize - Samaniego Vivanco, Tomás Daniel (2026)
Organomineral fertilizers (OMF) represent an opportunity to develop locally sourced fertilizers to decarbonize grain value chains. A two-location field study comparing OMF and mineral fertilizers (MF) agronomic and environmental performance was established at two Peruvian valleys, the environmental impacts of maize grain produced with locally produced OMF and imported MF were modelled through cradle-to-gate life cycle analysis (LCA). The carbon footprints (CF) of OMF resulted smaller than those of imported MF. Fully replacing MF with OMF results in equivalent grain yield, 43% higher phosphorus agronomic efficiency and reduced cradle-to-gate greenhouse gas (GHG) emissions in up to 232 kg carbon dioxide (CO₂) eq Mg⁻¹ grain. Estimated NOx emissions, nutrient lixiviation and mineral resource depletion were reduced as well, providing support for OMF as a tool for sustainable grain production.